Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/2162402x.2020.1784529
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor-infiltrating immune cells and prognostic validation of tumor-infiltrating mast cells in adrenocortical carcinoma: results from bioinformatics and real-world data

Abstract: Objective: The purpose of this study was to explore the composition of tumor-infiltrating immune cells (TIIC) and prognostic significance of tumor-infiltrating mast cells (TIMC) in adrenocortical carcinoma (ACC). Methods: The gene expression profiles of ACC were downloaded from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GSE90713, GSE12368). The abundance of TIICs in ACC samples was calculated by CIBERSORT algorithm and immunohistochemistry was used to identify mast cells of 39 tumor samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
(39 reference statements)
3
23
0
Order By: Relevance
“…In this study, we utilized multiplatform immunogenomic deconvolution to detangle the role of MC tumor infiltration and signaling activity within ACC TME. Our findings are multifaceted in that they support previous research characterizing TIMC abundance as a favorable prognostic factor in ACC 9 . Our analysis dives deeper to identify the optimal degree of TIMCs in the ACC microenvironment, delineate prognostic pro- and anti-tumorigenic MC signaling genes, and lay a foundation for future mechanistic studies and the development of new therapeutic interventions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we utilized multiplatform immunogenomic deconvolution to detangle the role of MC tumor infiltration and signaling activity within ACC TME. Our findings are multifaceted in that they support previous research characterizing TIMC abundance as a favorable prognostic factor in ACC 9 . Our analysis dives deeper to identify the optimal degree of TIMCs in the ACC microenvironment, delineate prognostic pro- and anti-tumorigenic MC signaling genes, and lay a foundation for future mechanistic studies and the development of new therapeutic interventions.…”
Section: Discussionsupporting
confidence: 89%
“…This study does not include single-cell analysis and the expression of genes analyzed in this study are likely not entirely of MC origin. Instead, this study aims to identify the potential activity of (but not limited to) MCs that may underly the prognostic significance in ACC TME that has now been deemed consistent across multiple methods of immunogenomic and immunohistochemistry quantification 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatics can help identify potential biomarkers of prognosis and progression, and in this way to predict survival outcomes in patients with cancer [ 9 , 10 ]. Long noncoding RNAs (lncRNAs) constitute a class of noncoding RNA molecules that regulate the growth of cancer cells and progression [ 11 ], and they are potential biomarkers to predict cancer risk and survival outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that infiltrating immune cells can be isolated from tumors suggesting that tumor immune infiltration is a crucial biological process that occurs as a result of immune cell migration from the blood into the TME ( Ge et al, 2019 ; R. Liu et al, 2020 ). Multiple reports have suggested that the proportion and functional alterations of different tumor infiltrated immune cells contribute to the initiation and progression of PAAD ( Meng et al, 2020 ; Tian et al, 2020 ). However, the regulatory mechanisms of immune cells, stromal components of TME, and tumor immune infiltration in PAAD remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%